“Chance volumes of the most miscellaneous character”: The Log Shanty Book-Shelves (1885-1898) of Reverend Henry Scadding - Murray, Heather (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada)

(untitled) (The Bibliographical Society of Canada/La Société bibliographique du Canada, 2025)
From 1885 to 1898, the Reverend Dr. Henry Scaddding (a polymathic Toronto cleric, local historian, and bibliophile) drew upon his extensive personal collection to curate annual book displays at the Toronto Industrial Exhibition. (These displays were staged under the aegis of the York Pioneers, and proved to be very popular.) While the annual themes differed over the years, each display was designed to demonstrate to visitors the state of “incipient lituratureism” in York (early Toronto), and the reading materials and reading tastes of the settler-reader. Scadding also used the accompanying catalogues to develop an original and somewhat eccentric theory of the operations of colonial cultural connectivity. Since Scadding had amassed perhaps the most important private library in nineteenth-century Toronto, the displays also show how he mobilized his collection for the purposes of public education. For book historians of today, the Log Shanty displays are of particular interest for their focus on reading culture and book access in pre-Rebellion Toronto.